2022
DOI: 10.3389/fpsyg.2022.953324
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the management student's entrepreneurial intentions: Role of entrepreneurship education and technology transfer

Abstract: Entrepreneurship education is considered as an important way to influence the competitiveness of any country or industry. Therefore, entrepreneurship education provides opportunities to progress to a more competitive educational environment. This paper examines the impact of students' entrepreneurship education in China on their entrepreneurial intentions. Perceived entrepreneurial capacity, education in entrepreneurship, and attitudes toward entrepreneurship are all factors in the model developed to predict e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…It is recommended that entrepreneurial courses and training programs carried out by educators should concentrate on cultivating cognitive factors; among which, educators and practitioners should pay regard to the role of EOI and PC collaboratively. On the one hand, educators should design strategies to increase university students' sense and ability of EOI, which can be addressed by experience-based learning processes, such as hands-on activities, simulation case studies, and business competition (Wang and Ortiz, 2022 ). On the other hand, having the necessary skills of EOI to initiate entrepreneurial activities alone is not necessarily leading to university students' entrepreneurial behaviors; educators need to equip students with positive psychological resources, such as PC, which can be developed and taught.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that entrepreneurial courses and training programs carried out by educators should concentrate on cultivating cognitive factors; among which, educators and practitioners should pay regard to the role of EOI and PC collaboratively. On the one hand, educators should design strategies to increase university students' sense and ability of EOI, which can be addressed by experience-based learning processes, such as hands-on activities, simulation case studies, and business competition (Wang and Ortiz, 2022 ). On the other hand, having the necessary skills of EOI to initiate entrepreneurial activities alone is not necessarily leading to university students' entrepreneurial behaviors; educators need to equip students with positive psychological resources, such as PC, which can be developed and taught.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was designed and validated based on a comprehensive review of the literature and input from experts in the fields of entrepreneurship and pharmacy. 8 , 16 Our survey instrument’s validation process was comprehensive and multifaceted. Pilot testing and face validity tests were conducted to improve clarity and context.…”
Section: Methodsmentioning
confidence: 99%
“…The existing studies in the literature have discussed the importance of student entrepreneurship for economic development based on their entrepreneurial intention (Zulfiqar et al, 2019). Nwosu et al (2022), Wang and Ortiz (2022) and Aparicio et al (2019) confirmed the entrepreneurial intention of the students is necessary to develop their entrepreneurial business. However, Tingting et al (2022) reported entrepreneurial behavior of students is developed when they have support from family (Lack eus, 2020), educational institutes (Xiang and Wang, 2022) and government (Hoang et al, 2022).…”
Section: Introductionmentioning
confidence: 92%